Type, number, and incidence. Recent patterns and differentials in relationship careers in Norway - Kenneth Aarskaug Wiik; Lars Dommermuth (Statistics Norway, Research Department, 2011)
Using data on individuals born 1946 to 1972 from the Norwegian Generations and Gender Survey (N = 7,587) we examine differentials in the number and incidence of co-residential relationships by gender and socioeconomic status. Regarding number of relationships, we found that women and younger respondents more often than men and older respondents reported having had two or more unions. 10% of the men and 5% of the women had no union experience by age 35. Controlling for relevant characteristics, our multivariate results showed that high income men experienced fewer unions than lower income men. Having a low income increased the odds of remaining single among men, whereas there was a positive association between tertiary education and remaining unpartnered among women.
Keywords: Z10; Z13; Z19; 330; Cohabitation; gender; GGS; marriage; Norway; relationship career; socioeconomic resources